A prospective study on rapid exome sequencing as a diagnostic test for multiple congenital anomalies on fetal ultrasound. (20th July 2020) - Corsten‐Janssen, Nicole; Bouman, Katelijne; Diphoorn, Janouk C. D.; Scheper, Arjen J.; Kinds, Rianne; el Mecky, Julia; Breet, Hanna; Verheij, Joke B. G. M.; Suijkerbuijk, Ron; Duin, Leonie K.; Manten, Gwendolyn T. R.; van Langen, Irene M.; et al.
Abstract: Objective: Conventional genetic tests (quantitative fluorescent‐PCR [QF‐PCR] and single nucleotide polymorphism‐array) only diagnose ~40% of fetuses showing ultrasound abnormalities. Rapid exome sequencing (rES) may improve this diagnostic yield, but includes challenges such as uncertainties in fetal phenotyping, variant interpretation, incidental unsolicited findings, and rapid turnaround times. In this study, we implemented rES in prenatal care to increase diagnostic yield. Methods: We prospectively studied 55 fetuses. Inclusion criteria were: (a) two or more independent major fetal anomalies, (b) hydrops fetalis or bilateral renal cysts alone, or (c) one major fetal anomaly and a first‐degree relative with the same anomaly. In addition to conventional genetic tests, we performed trio rES analysis using a custom virtual gene panel of ~3850 Online Mendelian Inheritance in Man (OMIM) genes. Results: We established a genetic rES‐based diagnosis in 8 out of 23 fetuses (35%) without QF‐PCR or array abnormalities. Diagnoses included MIRAGE ( SAMD9 ), Zellweger ( PEX1 ), Walker‐Warburg ( POMGNT1 ), Noonan ( PTNP11 ), Kabuki (KMT2D ), and CHARGE ( CHD7 ) syndrome and two cases of Osteogenesis Imperfecta type 2 ( COL1A1 ). In six cases, rES diagnosis aided perinatal management. The median turnaround time was 14 (range 8‐20) days. Conclusion: Implementing rES as a routine test in the prenatal setting is challenging but technically feasible, with a promising diagnostic yield and significant clinical relevance.